2016
DOI: 10.3899/jrheum.160648
|View full text |Cite
|
Sign up to set email alerts
|

Definition for Rheumatoid Arthritis Erosions Imaged with High Resolution Peripheral Quantitative Computed Tomography and Interreader Reliability for Detection and Measurement

Abstract: We propose a new definition for erosions visualized with HR-pQCT imaging. Interreader reliability for erosion detection is good, but further refinement of selection of landmarks for erosion size measurement, or automated volumetric methods, will be pursued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 19 publications
0
88
0
1
Order By: Relevance
“…Previous studies that compared patients with RA with healthy subjects using HR‐pQCT primarily focused on the visual detection of pathological interruptions . In a prior study, we demonstrated that with HR‐pQCT a variety of cortical interruptions can be seen in the finger joints of both patients with RA and healthy subjects.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies that compared patients with RA with healthy subjects using HR‐pQCT primarily focused on the visual detection of pathological interruptions . In a prior study, we demonstrated that with HR‐pQCT a variety of cortical interruptions can be seen in the finger joints of both patients with RA and healthy subjects.…”
Section: Introductionmentioning
confidence: 84%
“…(14) Previous studies that compared patients with RA with healthy subjects using HR-pQCT primarily focused on the visual detection of pathological interruptions. (14)(15)(16)(17)(18)(19)(20) In a prior study, we demonstrated that with HR-pQCT a variety of cortical interruptions can be seen in the finger joints of both patients with RA and healthy subjects. Some (larger) cortical interruptions had underlying trabecular bone voids and were suggestive of an erosion, whereas other cortical interruptions were smaller and may represent physiological interruptions (ie, vascular channels).…”
Section: Introductionmentioning
confidence: 94%
“…A cortical interruption was defined as a clear interruption of the cortex, seen on two consecutive slices on two orthogonal planes (on transverse, and on sagittal or coronal plane) [29,30]. …”
Section: Methodsmentioning
confidence: 99%
“…Anatomic pseudoerosions, i.e., normal concavities of a bone with a potential for misinterpreting them as arthritis-related erosions, were described in twelve original papers and reviews and may be classified into four types according to their anatomic form and configuration (Table 1): (1) a groove or notch or its incomplete form, i.e., a jutty, (2) a sulcus as part of an osteofibrous channel, (3) a subcapital neck on long bones, or (4) a nutritional channel or a zonal roughness [3,11,41,[51][52][53][54][55][56][57]. According to their shape, they may be grouped into (1) shallow or broad concavities and (2) subchondral cysts, if en-face displayed on an image and occasionally with a small opening to the joint space, or (3) channel-like structures (Figure 2a,c) [3,54,55].…”
Section: Anatomic Pseudoerosionsmentioning
confidence: 99%
“…The diagnosis of erosions and their quantification as part of radiographic scoring systems is an accepted surrogate biomarker of structural progression of arthritis [4,5]. Erosions in RA have been defined in consensus statements and in studies with high-resolution peripheral quantitative computed tomography (HRpqCT) as cortical defects, breaks, or other discontinuities with underlying trabecular bone loss and characteristic locations that can be identified with imaging [6][7][8][9][10][11][12]. diseases, clinical studies comparing therapeutic measurements in RA, studies comparing the sensitivity of imaging modalities without report of false positive diagnosed erosions or erosion-like lesions, surgical procedures or longitudinal studies without direct reference to this topic, case reports and conference papers.…”
Section: Introductionmentioning
confidence: 99%